Strategies to Reduce Children's Saturation in Distance Learning Through Power Point Presentation Media - Muhammad Maskur Musa; Abdul Khobir; Rohmah Nur Mahmudah (AL-ISHLAH: Jurnal Pendidikan, 2022)
Each of these individuals has an ability that is contained in each of them in expressing and utilizing these abilities, so in this case it is necessary to have an education in everyday life. Because with education in human life, it can increase the dignity, dignity and standard of living that are more in accordance with what humans aspire to in life. The purpose of this study was to determine strategies to reduce child boredom in distance learning (PJJ) through power point presentation media at Proyonanggan 02 Batang Elementary School during the COVID-19 pandemic in 2021. This research method used field research. The research approach used in this research is a qualitative approach. The results of this study explain strategies to reduce child boredom in distance learning (PJJ) through power point presentation media, namely: 1) Creating a new atmosphere in the classroom, 2) Carrying out creative and creative activities, 3) Relaxing in learning, 4) Performing strategies distance learning using power point. The obstacles faced in the strategy of reducing child boredom in distance learning (PJJ) through power point presentation media are 1). Internet Network Problems, 2) The ability of teachers and students to operate distance learning-based media, 3) PPT used in distance learning. The solution is that the slides used are then inserted in an interesting video, as well as pictures related to learning materials that are displayed very pleasantly, this then makes students no longer bored and of course enthusiastic about doing distance learning.Keyword: Strategies to Reduce Child Abortion; Distance Learning; Power Point